Dispositivo de inserção supercondutor em acelerador síncrotron: projeto magnético e simulação - Silva, João Henrique Ramos (2022)
Beamlines in synchrotron accelerators commonly require the installation of high-field magnets and insertion devices to produce high-energy radiation. High magnetic fields are an interesting issue that motivates the use of superconducting devices. In this work, three different preliminary magnetic models of a superconducting wavelength shifter (SWLS) were developed. Concerning the magnetic field, the goal was to develop a device capable of generating up to 7 T, within the optical specifications and operating margin previously determined, in order to adapt the SWLS in a straight section of a synchrotron accelerator. The results were obtained from computer simulations and discussed from the optimization of models’ geometric parameters to the analysis of the magnetic field spatial distribution.